The two solitudes of Canadian nativism: Explaining the absence of a competitive anti‐immigration party in Canada. Issue 4 (31st October 2019) - Gordon, Joshua; Jeram, Sanjay; van der Linden, Clifton
Abstract: Canada has been celebrated in popular and academic work for its relative immunity to nativist populism. No competitive nativist party has recently emerged in federal politics that challenges the mainstream consensus around mass immigration, unlike virtually every other postindustrial democracy. This paper argues that existing explanations for this "exceptionalism" are lacking. In particular, they fail to appreciate the importance of Quebec nationalism in contributing to this outcome. Quebec nationalism fractured the stronger anti‐immigration sentiment found in rural and smaller urban areas in both Quebec and Anglophone Canada and thereby prevented right‐wing parties from mobilising that sentiment in a way that could feasibly win elections. This forced such parties to moderate their message and court "ethnic voters" in suburban ridings around Toronto and Vancouver. We illustrate this argument using novel data which permit a comparison of the Canadian experience with nativist politics in Australia and New Zealand.